Peran bias perilaku investor dalam proses pengambilan keputusan dan kinerja investasi - Anwar, Roseline Mannuela; Wijaya, Hendry; Amelinda, Rita (Journal of Business & Banking, 2024)
This study aims to determine whether investor bias, including heuristic and herding biases, has an impact on investors’ investment behaviour, particularly in Indonesia. The sample was taken by purposive sampling, which is a non-probability sampling technique. This technique is used to identify respondents who have already made stock investments on the stock exchange. This study used 154 investor respondents, specifically those who started investing in stock from various range of age. The study employs path analysis using the Smart-PLS software tool for data analysis. The results of this study show that heuristic bias is proven to have a significant positive effect on investors’ investment decisions and performance. Furthermore, investment decisions are proven to mediate the effect of heuristic bias on investor investment performance. On the other hand, herding bias is not proven to have an effect on investor investment decisions and performance. In addition, investor investment decisions are also not proven to mediate the effect of herding bias on investor investment performance. Based on the results of this study, investors need to be aware of the role of heuristic bias to make more rational decisions that can ultimately improve investor investment performance.